Application of Plant Growth Regulators Mitigates Water Stress in Basil - Silva, Dayane Mércia Ribeiro (2024)
Abiotic stresses, such as water limitation, are significant limiting factors in basil production. One alternative to mitigate the harmful effects of this stress on plants is using plant growth regulators. This study’s objective is to evaluate different doses of plant regulators in basil under water deficiency conditions. A randomized block experimental design in a factorial scheme with two factors was used: the first factor referred to the water regimes of 50% and 100% stomatal conductance, the second to different doses of the plant regulator mixture: 0 mL L−1 (control), 3 mL L−1, 6 mL L−1, 9 mL L−1, and 12 mL L−1. Each treatment consisted of 12 pots per repetition. Biometric parameters, chlorophyll a fluorescence, and gas exchange were analyzed. The plant regulator positively influenced basil plants under water deficiency, with the most pronounced effects observed at the 12 mL L−1 dose: a 17% increase in the number of leaves, a fourfold increase in CO2 assimilation and carboxylation efficiency, and a sevenfold increase in water use efficiency. Therefore, the application of plant regulators on basil is recommended to mitigate the negative effects of water stress, with the most significant results observed at a dose of 12 mL L−1.